A new soft dielectric silicone elastomer matrix with high mechanical integrity and low losses1. Issue 14 (19th February 2015) - Madsen, F. B.; Yu, L.; Daugaard, A. E.; Hvilsted, S.; Skov, A. L.
<x xml:space="preserve">Abstract</x> Alkyl chloride-functional siloxane copolymers are synthesised as the basis for a new soft matrix for dielectric elastomers.